Literacy and extension services for improved livelihood in Nigeria (2019)
This paper focuses on literacy and extension Services for improved livelihood in Nigeria. Extension in this context involves the transfer of educational activity, programmes and advisory Services to people, based on their needs, aspirations as well as problems; and is designed to ensure progress towards the attainment of needs and facilitate the application of new knowledge for improved livelihood. Literacy, on the other hand, is the ability of individuals to identify, understand, interpret, create, communicate, and compute using printed and written materials associated with varying contexts; while livelihood goes beyond poverty eradication, and extends to include factors and processes that could enhance or hinder an individual’s ability to make a living